Hepatite b: uma análise epidemiológica no estado do Pará entre 2010 a 2020 - SILVA, Felipe Emanuel Roque da (2024)
The objective of the study is the epidemiological analysis of hepatitis B in the State of Pará, from 2010 to 2020. It is a cross-sectional, descriptive, retrospective study with a quantitative and documental approach based on the records of cases of hepatitis B notified in the System of Information on Notifiable Diseases, available for consultation in the database of the Department of Informatics of the Unified Health System (DATASUS). A total of 2,759 cases were found and the analyzes of the variables were divided into: sociodemographic profile (geographical distribution, sex, age group, race, education, in addition to the evaluation of the special population of pregnant women and vertical transmission) and clinical profile of the disease (hepatitis acute, chronic, fulminant and undefined cases). According to the analysis of the variables, the following results were observed: the analysis of the sociodemographic profile pointed to the region of the lower Amazon, Carajás and Metropolitana I as the region with the highest prevalence, with 1,846 cases (67%); the predominant female gender with 1,401 (67%) cases; the age group from 20 to 39 years old with 1,333 (49%) cases; schooling with complete secondary education with 576 (21%) cases, brown race with 2,213 (81%) cases. Among the special population of pregnant women, 519 (18.1%) cases were reported, with the second trimester being the most prominent with 219 (42%) cases. Finally, the evaluation regarding vertical transmission with about 18 (0.6%) cases. In view of this, it is concluded that hepatitis is still a public health problem in the northern region of the country and in the state of Pará, requiring measures such as expanding testing, increasing vaccination coverage and education in reproductive health, since transmission sexual is still the most frequent.